Consumer Description Analysis Of Realme Smartphone Product Quality On Customer Satisfaction (Case Study in Bengkalis Community) - Rini Arvikasari (Universitas Islam Lamongan, 2022)
This study aims to determine the quality of realme smartphone products based on the level of user satisfaction, especially in the Bengkalis area. This research is a descriptive quantitative study that describes the responses of smartphone users from the Bengkalis realme. The sample in this study was a hundred users of realmee smartphone products. Based on the results of the analysis of the questionnaire that has been divided, it can be seen that all indicators get a good average score. Thus, it can be concluded that realme products have good quality and provide satisfaction for users or customers